2018
DOI: 10.1002/jcp.27611
|View full text |Cite
|
Sign up to set email alerts
|

CCN2 promotes drug resistance in osteosarcoma by enhancing ABCG2 expression

Abstract: In recent years, osteosarcoma survival rates have failed to improve significantly with conventional treatment modalities because of the development of chemotherapeutic resistance. The human breast cancer resistance protein/ATP binding cassette subfamily G member 2 (BCRP/ABCG2), a member of the ATP‐binding cassette family, uses ATP hydrolysis to expel xenobiotics and chemotherapeutics from cells. CCN family member 2 (CCN2) is a secreted protein that modulates the biological function of cancer cells, enhanced AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…29 Moreover, xenograft experiments conducted by Tsai et al suggested that CCN2 upregulation protected OS cells from doxorubicin, and the therapeutic efficacy was remarkably promoted when CCN2 was reduced. 30 However, the relevance of CCN2 in chemoresistance of OS cells to DDP and taxanes was not clarified yet, which might be the direction for our further experiments.…”
Section: Discussionmentioning
confidence: 96%
“…29 Moreover, xenograft experiments conducted by Tsai et al suggested that CCN2 upregulation protected OS cells from doxorubicin, and the therapeutic efficacy was remarkably promoted when CCN2 was reduced. 30 However, the relevance of CCN2 in chemoresistance of OS cells to DDP and taxanes was not clarified yet, which might be the direction for our further experiments.…”
Section: Discussionmentioning
confidence: 96%
“…High ABCG2 expression has been identified in a variety of solid tumors and has been correlated with poorer clinical outcomes [8][9][10]. In a recent study, Tsai et al [18] reported that ABCG2 overexpression could decrease the therapeutic effect of DOX in OS cells. For the first time, we confirmed the role of ABCG2 in the development of chemoresistance using the established DOX-resistant OS cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the Notch pathway resulted in downregulation of MRP1 expression, overcoming chemoresistance in human OS cells (Li et al, 2016). BCRP upregulation was reported to be a reason of CCN2 overexpression‐caused promotion of doxorubicin resistance (Tsai et al, 2019). Therefore, we concluded that poncirin overcame cisplatin resistance in cisplatin‐resistant OS cells by downregulating MDR1, MRP1, and BCRP.…”
Section: Discussionmentioning
confidence: 99%